Analisis Ketimpangan Pembangunan Ekonomi Antar Kabupaten/Kota Di Provinsi Jambi - Susilawati . (Sekolah Tinggi Ilmu Ekonomi STEMBI Bandung, 2015)
Economic growth of districts in Jambi Province during the period 20042013 varied enough. This indicate that there are the disparities economic development between regions. This research aims to analyze disparities economic development in terms of regional income disparities and how the correlation between economic growth and the disparities of economic development during the period 2004-2013. The analysis used Williamson Index and Pearson Correlation as the instrument. From the research note that economic development disparities between districts in Jambi Province are moderate and correlations between economic growth and the disparities of economic development are weak and negative. To reduce disparities of economic development occuring need the strategic policies of the regional development for all of regions.